1994
DOI: 10.1093/ajh/7.5.381
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Blood Pressure and Left Ventricular Mass in the Young: The Hypertension in Pregnancy Offspring Study

Abstract: The present study evaluates potential predictors for the future blood pressure and left ventricular mass in children. Fifty-two children were studied at mean age 12.6 +/- 1.5 years and reexamined after 5.6 years. Thirty-six children were born to mothers who had hypertension during pregnancy and 16 children were born after normotensive pregnancies by mothers who remained normotensive at follow-up. Blood pressure was measured at rest and during physical exercise. Left ventricular mass was calculated from M-mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…1 Gender differences in blood pressure emerge during adolescence and persist through adulthood. 7,8 In all ethnic groups, younger men tend to have higher mean systolic and diastolic blood pressure than younger women (by 6-7 mm Hg and 3-5 mm Hg respectively), and through middle age, hypertension is more prevalent among men than women ( Figure 1). 9 However, hypertension is more prevalent among women than men after age 59.…”
Section: Epidemiologymentioning
confidence: 99%
“…1 Gender differences in blood pressure emerge during adolescence and persist through adulthood. 7,8 In all ethnic groups, younger men tend to have higher mean systolic and diastolic blood pressure than younger women (by 6-7 mm Hg and 3-5 mm Hg respectively), and through middle age, hypertension is more prevalent among men than women ( Figure 1). 9 However, hypertension is more prevalent among women than men after age 59.…”
Section: Epidemiologymentioning
confidence: 99%
“…Further research should focusIntroduction Most European studies have consistently shown lower blood pressure (BP) levels in women than in men. [1][2][3][4] This sex difference in BP in populations of European descent appears during adolescence and persists up to the age of 60 years. 3,5 The mechanisms underlying the sex difference in BP are not well understood, but sex hormones have been suggested as a possible cause.…”
mentioning
confidence: 99%
“…[1][2][3][4] This sex difference in BP in populations of European descent appears during adolescence and persists up to the age of 60 years. 3,5 The mechanisms underlying the sex difference in BP are not well understood, but sex hormones have been suggested as a possible cause. [6][7][8] The favourable position among women in terms of BP and hypertension is not as clearly observed in South Asian descent populations compared with others.…”
mentioning
confidence: 99%
“…The sex difference in hypertension was widely observed in various populations (28). Most European studies have shown lower blood pressure levels in women than in men (29)(30)(31)(32). Such sex differences in hypertension between European populations appear during adolescence and persist up to the age of 60 (33,34).…”
Section: What Is Knownmentioning
confidence: 99%